2021
DOI: 10.1371/journal.pone.0256688
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 pandemic on grade inflation in higher education in Turkey

Abstract: This study analyzes the effects of the COVID-19 pandemic on grade inflation in higher education. Data were collected from five universities in Turkey, including grades of 152,352 students who attended 2,841 courses conducted by 903 instructors before the COVID-19 pandemic and grades of 149,936 students who attended 2,841 courses conducted by 847 instructors during the COVID-19 pandemic. The results of this study demonstrate that the COVID-19 pandemic causes a marginal increase in grades in higher education whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 48 publications
1
21
0
3
Order By: Relevance
“…Supriya et al (2021) [21] conducted a study in the United States comparing a traditional online biology course to an in-class biology course that transitioned to on-line; grades were slightly higher for both compared to previous semesters. Karadag (2021) [22] noted a small amount of grade inflation during COVID-19 as compared to previous semesters. Although students' grades were higher, students reported a negative impact on their learning, interactions with peers and instructors, feeling part of a campus community and career preparation.…”
Section: Discussionmentioning
confidence: 97%
“…Supriya et al (2021) [21] conducted a study in the United States comparing a traditional online biology course to an in-class biology course that transitioned to on-line; grades were slightly higher for both compared to previous semesters. Karadag (2021) [22] noted a small amount of grade inflation during COVID-19 as compared to previous semesters. Although students' grades were higher, students reported a negative impact on their learning, interactions with peers and instructors, feeling part of a campus community and career preparation.…”
Section: Discussionmentioning
confidence: 97%
“…Grade inflation has been reported across many aspects of higher education. With instructors potentially compensating for unforeseen negative circumstances (Karadag, 2021 ). Grade inflation has been a topic of conversation and academic study for many decades now (Astin, 1998 ; Eiszler, 2002 ; Popov & Bernhardt, 2013 ), but it is difficult to assess whether student attainment may have improved due to a reduction in their social life and other factors or due to differences in assessment grading.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, recent findings related to the Covid-19 situational context of online teaching suggest an inflation of grades during this period. In a study by Karadag (2021), he found that the pandemic caused a marginal increase in grades in higher education in Turkey. Similarly, in another study, Sparks (2022) reported that students' grades ratcheted up in 2019 and the pace accelerated during the pandemic.…”
Section: Impact Of Covid-19 Online Instruction On Students' Gpa Scoresmentioning
confidence: 99%